Development of Animated Video Learning Media for Energy Saving Behavior at Robbani Tutoring in Ogan Ilir Regency - Ahmania, Ayunda; Husin, Azizah; Nurrizalia, Mega (UNDIKMA, 2023)
The aim of this research is to develop learning media for animated videos of energy saving behaviour at Robbani Tutoring in Ogan Ilir Regency. The model suggested by Thiagarajan in terms of defining, designing, developing and disseminating (the 4-D model) is used as a development model. The data were collected by means of questionnaires and interviews. The results of this study indicate that validation from linguists obtained a percentage score of 88.8% with a very feasible category, media experts obtained a percentage score of 90% with a very feasible category, and material experts obtained a percentage score of 97% with a very feasible category. The results of one-to-one trial showed an overall percentage score of 79% with a very practical category and the same was true for the small group trial, which scored 89% in that category. Therefore, it is considered that it is feasible and practical to use the animated video product of energy saving behaviour as a learning media in science subjects for students to learn about energy saving behaviour.